An unusual penetrating hand injury from a hurling helmet. Issue 12 (December 2015) - Joyce, C.W.; Kelly, E.J.
Abstract: We report on an unusual case of a penetrating injury from a bar from a metal grille from a hurling face protector. The bar impaled the patient's thumb after a collision with a patient. The bar was surgically removed in theatre with minimal injury. The authors highlight the need to ensure that helmets and face protectors are regularly checked, particularly ensuring that the bars have not become detached.